2023
DOI: 10.1002/cam4.6226
|View full text |Cite
|
Sign up to set email alerts
|

A study of clinical and molecular characteristics in bilateral primary breast cancer

Abstract: BackgroundBilateral primary breast cancer (BPBC) is a rare type of breast cancer. Studies on the clinicopathologic and molecular characteristics of BPBC in a metastatic context are very limited.MethodsA total of 574 unselected metastatic breast cancer patients with clinical information were enrolled in our next‐generation sequencing (NGS) database. Patients with BPBC from our NGS database were regarded as the study cohort. In addition, 1467 patients with BPBC and 2874 patients with unilateral breast cancer (UB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Family members can understand their genetic risks through genetic counseling and undergo appropriate screening and management based on the recommendations of healthcare professionals. Moreover, studies have found that the infiltrating ductal type is the most common histology in BBC ( 22–24 ). Some studies indicate that the survival rates of patients with unilateral and BBC are comparable ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Family members can understand their genetic risks through genetic counseling and undergo appropriate screening and management based on the recommendations of healthcare professionals. Moreover, studies have found that the infiltrating ductal type is the most common histology in BBC ( 22–24 ). Some studies indicate that the survival rates of patients with unilateral and BBC are comparable ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…10 Patients with HR + BC have a higher proportion of contralateral BC than HR-or HER2+, whether synchronous bilateral breast cancer (BBC) or metachronous BBC. 11,12 Currently, patient with BBC whom is considered to have a poorer prognosis and is frighted to physicians and patients, moreover, the number of metachronous BBC is increasing with the prolongation of overall survival of patients with BC, 13 especially in patients with N + Luminal B (HER2-) BC.…”
Section: Introductionmentioning
confidence: 99%
“…Bilateral breast cancers, an uncommon form and accounting for 3–5% of all breast cancers cases, happens when women develop breast cancers in both breasts, with the second primary cancer in the contralateral breast being either synchronous or metachronous [ 3 7 ]. Synchronous bilateral breast cancers are diagnosed 6–12 months apart and represent about 1% of breast cancers [ 8 10 ]. Clinically, patients with synchronous bilateral breast cancers behaved similarly to those with unilateral breast cancers [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%